General Situation Analysis of the E-Commerce Sector in The World and in Turkey: Opportunities and Challenges - MANGIR, Fatih; ALLAHVERDİ, Zehra Feryal (Cyberpolitik Journal, 2023)
The shift in production and consumption patterns due to the effect of the Covid-19 pandemic has increased the integration of information technologies into production and consumption so that the development pace of the e-commerce sector in the world and in Turkey has gained momentum. While businesses that have completed the digitalization process around the world with the pandemic have easily adapted to the difficult situation in the economy, businesses that do not have sufficient infrastructure have increased their investments to compete in the market. E-commerce has difficulties such as product variety, shopping without a time limit, price comparison, cost advantage, opportunities such as reaching wider audiences, cyber security, product return difficulties, and high logistics costs. Turkey has developed in e-commerce over the years, has made progress in digitalization, and has the potential to increase e-commerce with the advantage of the young population. In this study, the general outlook, opportunities, and challenges of e-commerce in Turkey and in the world are analyzed.